"Like Walking into an Empty Room": Effects of Eurythmy Therapy on Stress Perception in Comparison with a Sports Intervention from the Subjects' Perspective—A Qualitative Study. (10th March 2015) - Berger, B.; Bertram, M.; Kanitz, J.; Pretzer, K.; Seifert, G.
Abstract : Background . Stress and health-related quality of life are important constructs used in treatment evaluation today. This study is based on a randomised controlled trial examining the stress-reducing effect of eurythmy therapy in comparison with step aerobics in 106 healthy but stressed subjects. The aim of the analysis was to characterise changes in the subjective perceptions of the participants. Methods . Interviews were conducted with 76 healthy adults, 36 (f = 31 / m = 5 ) from the eurythmy group and 40 (f = 28 / m = 12 ) from the step aerobics group both analysed by content analysis and phenomenologically. Results . The following categories were identified for the eurythmy therapy group: enabling a productive therapeutic response, emergence of a new perceptual space, reevaluation of the accustomed perception, and emergence of new options for action . Step aerobics places increased physical and intellectual demands. These are perceived differently as pleasant and relaxing, insufficiently challenging and/or boring, and too challenging and thus experienced as stress-enhancing. Conclusion . The qualitative results provided revealing insights into the profound effects of and subjective assignments of meaning to external and internal stress factors. Processes of mental reinterpretation leading to stress reduction can be stimulated by physical procedures such as eurythmy therapy.